Modelling rail thermal differentials due to bending and defects - Bosomworth, Chris; Spiryagin, Maksym; Alahakoon, Sanath; Cole, Colin (Transport, 2021)
Rail foot flaws have the potential to cause broken rails that can lead to derailment. This is not only an extremely costly issue for a rail operator in terms of damage to rolling stock, but has significant flow-on effects for network downtime and a safe working environment. In Australia, heavy haul operators run up to 42.5 t axle loads with trains in excess of 200 wagons and these long trains produce very large cyclic rail stresses. The early detection of foot flaws before a broken rail occurs is of high importance and there are currently no proven techniques for detecting rail foot flaws on trains at normal running speeds. This paper shall focus on the potential use of thermography as a detection technique and begin investigating the components of heat transfer in the rail to determine the viability of thermography for detecting rail foot flaws. The paper commences with an introduction to the sources of heat generation in the rail and modelling approaches for the effects of bending, natural environmental factors and transverse defects. It concludes with two theoretical case studies on heat generated due to these sources and discusses how they may inform the development of a practical thermography detection methodology.